COLERIDGE'S MORAL ODYSSEY: THEMES OF GUILT AND PENITENCE IN 'THE RIME OF THE ANCIENT MARINER' - Srivastava, Himanshu A. (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This study examines "The Rime of the Ancient Mariner" by Samuel Taylor Coleridge from the perspective of guilt and penitence. The moral odyssey of the mariner, whose rash act of shooting an albatross sets off a sequence of paranormal happenings and spiritual reflection, is explored in depth in Coleridge's poetic song. In order to demonstrate how themes of nature, guilt, and redemption are relevant to the larger literary movement, the analysis starts with a study of Coleridge's biography and the setting of the Romantic age. Coleridge's own experiences with addiction and remorse give the poem a deeper personal meaning that enhances its examination of moral duty and human weakness. The poem's episodic storytelling and symbolic imagery, together with its narrative structure, highlight the moral and psychological ramifications of guilt. Coleridge illustrates the transformational power of moral contemplation and spiritual regeneration via the mariner's slow decline into guilt-ridden despair and eventual struggle for redemption. The symbolism of the albatross, which at first represented the grace of nature and the mariner's relationship to it, subsequently changed to represent a load of guilt and served as a catalyst for the mariner's spiritual path towards penitence, is central to the interpretation. The poem's religious and spiritual undertones deepen its thematic depth by evoking Christian allegory and concepts of divine forgiveness. At the end, the research sheds light on Coleridge's timeless observations on the moral complexity of life and the human conscience. As a monument to Coleridge's literary prowess and moral philosophy, "The Rime of the Ancient Mariner" provides readers with timeless insights about guilt, penitence, and the pursuit of spiritual salvation.